An analysis of the impact of the sanitary and phytosanitary agreement on market access : case study on the SA/EU citrus dispute and AGOA dispute - Singh, Shikira (University of KwaZulu-Natal, 2016)
Abstract not available.
Keywords: AGOA; African Growth and Opportunity Act; Cooperation Agreement; Market access; Sanitary and Phytosanitary (SPS) Agreement; Trade Development; Trade barrier; WTO; World Trade Organization